Genome-Wide Analysis of Barrett's Adenocarcinoma. A First Step Towards Identifying Patients at Risk and Developing Therapeutic Paths - Dai, Yiyang; Wang, Qing; Gonzalez Lopez, Adrian; Anders, Mario; Malfertheiner, Peter; Vieth, Michael; Kemmner, Wolfgang (Translational Oncology, 2018)
BACKGROUND: Barrett's esophagus metaplasia is the key precursor lesion of esophageal adenocarcinoma. The aim of this study was to find a subset of markers that may allow the identification of patients at risk for esophageal adenocarcinoma, and to determine genes differentially expressed in esophageal squamous cell carcinoma. METHODS: Laser capture microdissection technique was applied to procure cells from defined regions. Genome-wide RNA profiling was performed on esophageal adenocarcinoma (n = 21), Barrett's esophagus (n = 20), esophageal squamous carcinoma (n = 9) and healthy esophageal biopsies (n = 18) using the Affymetrix Human Genome U133plus 2.0 array. Microarray results were validated by quantitative real-time polymerase chain reaction in a second and independent cohort and by immunohistochemistry of two putative markers in a third independent cohort. RESULTS: Through unsupervised hierarchical clustering and principal component analysis, samples were separated into four distinct groups that match perfectly with histology. Many genes down-regulated in esophageal cancers belong to the epidermal differentiation complex or the related GO-group “cornified envelope” of terminally differentiated keratinocytes. Similarly, retinol metabolism was strongly down-regulated. Genes showing strong overexpression in esophageal carcinomas belong to the GO groups extracellular region /matrix such as MMP1, CTHRC1, and INHBA. According to an analysis of genes strongly up-regulated in both esophageal adenocarcinoma and Barrett's esophagus, REG4 might be of particular interest as an early marker for esophageal adenocarcinoma. CONCLUSIONS: Our study provides high quality data, which could serve for identification of potential biomarkers of Barrett's esophagus at risk of esophageal adenocarcinoma progression.
CRIS-Team Scopus Importer:2025-03-05